Ecological and Nutritional Functions of Agroecosystems as Indicators of Smallholder Resilience - Stratton, Anne Elise; Kuhl, Laura; Blesh, Jennifer (Frontiers in Sustainable Food Systems, 2020)
Smallholder agriculture is the foundation of global food systems, yet smallholders face severe socio-economic and environmental challenges that can destabilize livelihoods and threaten their resilience. Given that smallholder farmers rely on household production to meet their nutritional needs, management of soil fertility, biodiversity, and other ecological characteristics of agroecosystems directly affects smallholders' capacity to produce sufficient crop nutrients for their diets. However, we lack explicit frameworks linking ecological and nutritional functions of agroecosystems, as well as research exploring farmers' adaptive capacity and agency in mediating these functions, and ultimately, agroecosystem resilience. To address these gaps, we developed an indicator framework to evaluate the complementary roles of ecological and nutritional functions of agroecosystems for smallholder resilience. Paired ecological and nutritional indicators were aggregated into an index representing four agroecosystem functions: (1) Productivity, (2) Diversity, (3) Quality, and (4) Functional Diversity. We then applied this framework and index to a case study of Q'eqchi' Maya smallholders in eastern Guatemala, using farm management and crop quality data from 60 households to determine the status of agroecosystem functions and assess coping and adaptive capacities in response to shocks. More than three-quarters of farms in the sample relied solely on household production of staples to meet their nutritional demands. Across farms, ecological and nutritional indicators were significantly related (Kendall's tau = 0.58, z = 5.7, p < 0.0001), and we found both synergistic (Quality, Functional Diversity) and tradeoff (Productivity) relationships between indicator pairs. We found that farmers using ecological adaptation strategies such as cover cropping and agroforestry had significantly higher levels of agroecosystem functioning and resilience than farmers who were coping with shocks by working off-farm or renting land from plantations. Our findings demonstrate the importance of linking ecological and nutritional functions of agroecosystems through diversified management practices to leverage their synergies. Because smallholder agroecosystems underlie a third of the food system, understanding and promoting their resilience is critical for the social, ecological, and nutritional well-being of global populations.